Moderate to Severe Diarrhea and Associated Factors Among Under-Five Children in Wonago District, South Ethiopia: A Cross-Sectional Study - Tesfaye TS; Magarsa AU; Zeleke TM (Dove Medical Press, 2020)
Tinsae Shemelise Tesfaye,1 Abowak Ulfata Magarsa,2 Tadesse Mekonen Zeleke3 1Department of Public Health, College of Health Science and Medicine, Dilla University, Dilla, Ethiopia; 2Primary Health Care Unit, Adegalchati Health Center, Elwaye, Ethiopia; 3Food Science, and Nutrition Directorate, Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Tinsae Shemelise TesfayeDepartment of Public Health, College of Health Science and Medicine, Dilla University, Dilla, EthiopiaTel +251910644517Email justtinsae@gmail.comBackground: Diarrheal disease is the second leading cause of death in children under five years old and is responsible for killing around 525 000 children every year. Based on the world health organization estimates, diarrhea contributes to more than one in every ten (13%) child deaths in Ethiopia. Despite the emphasis given to improving child health, many children are still dying due to easily preventable and treatable diarrheal disease in Ethiopia.Methods: A community cross-sectional study was conducted on randomly selected under-five children who live in Wonago district. Three hundred eighteen households were selected using a systematic sampling technique. Data were collected using a structured closed-ended questionnaire. Data were cleaned, coded, and entered into the statistical package for social sciences window version 20 statistical software analysis.Results: The magnitude of moderate to severe diarrhea in the Wonago district was 30.9%. The number of family members (AOR: 2.7, 95% CI [1.277– 5.716]), presence of animals in households (AOR: 2.591, 95% CI [1.188– 5.650]), availability of latrine (AOR: 2.129, 95% CI [1.006– 4.505]), and hand washing practice during a critical time (AOR: 2.683, 95% CI [1.139– 6.319]) were strongly associated with moderate to severe diarrhea.Conclusion: Childhood diarrhea remains an important health concern in the study area. This calls for a holistic and multimodal approach for the prevention, early identification, and intervention of diarrhea in children. More emphasis should also be given on personal, household, and environmental hygiene, as well as family planning.Keywords: diarrhea, children, South, Wonago, Ethiopia